Influences of pine plantations on small mammal assemblages of the Patagonian forest-steppe ecotone - Lantschner, Maria Victoria; Rusch, Veronica Elena; Hayes, John P. (De Gruyter, 2019)
The management of forested landscapes for biodiversity conservation is increasingly recognized as an important objective in Argentina. However, pine plantations are being established replacing native pristine or human modified vegetation and there is a lack of information of its impact on biodiversity. To understand the effect of this activity on small mammal assemblages, we compared its composition and abundance in pine plantations and native vegetation dedicated to traditional cattle production and studied the habitat structure that could explain the differences between habitat types. Additionally, we evaluated the role of firebreaks as corridors in forested landscapes. We found lower abundance and fewer species in plantations. Firebreaks showed a lower abundance and number of species than native vegetation, suggesting that they do not function effectively as corridors. Abrothrix longipilis was the most frequently captured species and abundance of this species was best explained by herbaceous cover and shrub richness. Our results suggest that pine plantations negatively impacts small mammal assemblages and that the decline is strongly associated with decreased understory cover and plant species richness. Management practices targeting conservation objectives such as maintaining lower tree densities and retention of native understory could enhance the value of forest plantations as habitat for small mammal species.